Effect of L-isoleucine and L-phenylalanine Addition on Aroma Compound Formation During Longan Juice Fermentation by a Co-culture of Saccharomyces cerevisiae and Williopsis saturnus - Trinh, T.T.T.; Woon, W.Y.; Yu, B.; Curran, P.; Liu, S.-Q. (South African Journal of Enology and Viticulture, 2016)
Some amino acids are known to be precursors of aroma-active compounds produced by yeast metabolism. This study examined the effect of the addition of L-isoleucine and L-phenylalanine on the volatile profiles of longan wine fermented by a co-culture of Saccharomyces cerevisiae var. bayanus EC-1118 and Williopsis saturnus var. saturnus CBS254 inoculated at a ratio of 1:1 000 cfu/mL with the aim of enhancing longan wine aroma. Significantly higher concentrations of active amyl alcohol (2-methyl-1-butanol), 2-phenylethyl alcohol and their corresponding acetate esters were found in the longan wine with added L-isoleucine and L-phenylalanine respectively, compared with the control (without added amino acids). The biosynthesis of other volatile compounds was either similar or minimally different, although the formation of some acetate esters, such as isoamyl acetate, hexyl acetate and ethyl acetate, was decreased. These results suggest that the added amino acids play an important role in enhancing the production of targeted aroma compounds in longan wine fermented with mixed yeasts, and that the addition of selected amino acids can be a valuable tool to modulate the formation of aroma compounds in longan wine.